2010
DOI: 10.2174/157340110791233256
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effects of Dietary Biogenic Amines

Abstract: Biogenic amines (BAs) are defined as low molecular weight organic bases with biological activity. They are formed and degraded as part of the normal metabolism of microorganisms, plants and animals, in which they have important physiological functions. In humans, BAs are involved in brain activity, the regulation of body temperature and stomach pH, gastric acid secretion, the immune response, and cell growth and differentiation etc. However, the consumption of foods with high concentrations of BAs can induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
294
2
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(325 citation statements)
references
References 61 publications
1
294
2
5
Order By: Relevance
“…Nonetheless, with the high level of BA monitoring in food products [23], it is equally important to determine the identity of bacterial strains and influence of the production of BAs by the resident microbiota in the human gut, independently from consumption of these BAs. Our data suggest that many different microbial species can produce, utilize or degrade BAs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, with the high level of BA monitoring in food products [23], it is equally important to determine the identity of bacterial strains and influence of the production of BAs by the resident microbiota in the human gut, independently from consumption of these BAs. Our data suggest that many different microbial species can produce, utilize or degrade BAs.…”
Section: Discussionmentioning
confidence: 99%
“…The best known reactions are those caused by histamine. Histamine is known to cause rash, edema, headaches, hypotension, vomiting, palpitation, diarrhea, and heart problems (Ladero et al, 2010). Tyramine and phenylethylamine can produce hypertension through the release of noradrenalin and norepinephrine, respectively, which are vasoconstrictors.…”
Section: Toxicological Effect Of Biogenic Amines (Ba) In Winesmentioning
confidence: 99%
“…Beside the toxic effect (Ladero et al, 2010), some BA also have other negative consequences, particularly regarding sensory characteristics of wine and thus economic implications. A study carried out by Rohn et al (2005) showed that high contents of histamine in wines identify well-trained wine assessors.…”
Section: Toxicological Effect Of Biogenic Amines (Ba) In Winesmentioning
confidence: 99%
“…Those molecules are synthetized by micro-organism on human, animal and plants tissus (Ladero, Calles-Enríquez, Fernández, & Alvarez, 2010). This synthesis is done through the amino acid decarboxylation metabolic way.…”
Section: Introductionmentioning
confidence: 99%